MENCARI KARAKTER PENDIDIK YANG IDEAL BAGI INDONESIA (Dalam Cerita dan Realita dari Masa ke Masa) - Wicaksono, Andri (Lentera: Jurnal Ilmiah Kependidikan, 2017)
The idea of mental revolution stems from people's perceived turmoil in various spheres of life that mental revolution must be done immediately. Given, first, the failure of the New Order regime in carrying out development, which has not touched the paradigm, mindset, or political culture in the framework of nation building. Mentality problem the nation is part of the cultural issues (culture). Therefore, one way to change it must be through cultural ways as well, namely through education. Mental revolution starts from education, considering the role of education is very strategic in shaping the child's mentality of the nation. Development of culture and character of the nation is realized through the realm of education. In other words, the mental revolution must begin in the classroom, that teachers should be at the forefront in realizing these ideals. In this study are revealed various things that include the idea of the beginning of the mental revolution in this country, the mental revolution for educators: the embodiment of indonesian human self, and the character of educators; a mental revolution.